Narcissism Today: What We Know and What We Need to Learn. (December 2021) - Miller, Joshua D.; Back, Mitja D.; Lynam, Donald R.; Wright, Aidan G. C.
Narcissism is of great interest to behavioral scientists and the lay public. Research across the past 20 years has led to substantial progress in the conceptualization, measurement, and study of narcissism. This article reviews the current state of the field, identifying recent advances and outlining future directions. Advances include hierarchical conceptualizations of narcissism across one-factor (narcissism), two-factor (grandiose vs. vulnerable narcissism), and three-factor (agentic extraversion, antagonism, narcissistic neuroticism) levels; the development of measures to assess the components of narcissism; clarification of the relations between narcissism and self-esteem; an understanding of the behavioral and motivational dynamics underlying narcissistic actions and social outcomes; and insight regarding potential fluctuations between narcissistic states. Future directions point in general to increased research using the lower levels of the narcissism hierarchy, especially the three-factor level. At this level, more research on the etiology, heritability, stability, and centrality of the three components is required.